Field Evaluation of New Fungicide, Etisa 80 WP for Management of Tomato Late Blight (Phytophthora infestans (Mont) de Bary) in Rift valley of, Ethiopia - Begna, Feyissa (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Tomato (Lycopersicon esculentum Mill.) is one of the most important vegetables worldwide. World tomato production in 2014 was about 125 million tons of fresh fruit from an estimated 4.1 million ha (FAOSTAT, 2011). Among vegetables crop grown in Ethiopia tomato ranks first both in area coverage and yield per acre. The experiment was conducted at Adami Tulu Agricultural Research Center during off season (November 2015 – March, 2016), to evaluate the efficacy of fungicide with trade name of Etisa 80% WP and common name Mancozeb with the active ingredient content of Mancozeb 800g/kg WP for controlling tomato late blight caused by Phytophthora infestans Significantly highest (80%) Phytophthora infestans severity score was observed on untreated pots while significantly lowest (26.6 - 28.3) severity score was recorded in all fungicide treated plots. The minimum disease severity score (26.6%) was obtained from plot treated with Sabozeb 80% WP (Standard check) at 2.5 kg ha-1. The result showed no significant difference between Sabozeb 80% WP and Etisa 80% WP. Significantly, highest (228 ha-1) weight of marketable tomato yield was obtained from plots treated with Etisa 80% WP at rate of 2.5kg ha-1 followed by Sabozeb 80% WP (220.7) at the same rate. The result of the two indicated non-significant difference with in the treatments. However, significantly lowest (93 q ha-1) yield was obtained from untreated plots.. Based on the results of the this location test carried out in rift valley, Ethiopia on the effectiveness of the test fungicide, Etisa 80% WP, and consideration of the wide range of late blight disease in tomato controlled, the use of Etisa 80% WP by the farming community (both individually and or private sector) will no doubt improve tomato production in Rift Valley as well as in similar agro-ecology.